Estudio de prefactibilidad para la implementación de una planta productora de infusiones de hojas de guanábana (Annona muricata) endulzado con hojas de stevia (Stevia rebaudiana) - Granda Toro, Renzo (2022)
The objective of the research is to determinate the market, technical, economic, financial and social viability for the installation of a soursop infusions plant sweetened with stevia. The sale of the product will to people who belong to the socioeconomic level A and B of Lima Metropolitana. The areas that have a greater amount of population who belong to these levels are zones 6 and 7 of Lima and have 8.77% of the city's inhabitants. The price of the product will be S/ 12 and it will be sold in supermarkets. The production plant will be in Junín in the Huancayo province. The plant size is 186 655 bag per day in the last year and it will be defined by the market. The technology required to produce the tea bags is feasible to acquire and use. The investment in assets amounts to S// 969 466.91 and the working capital to S/176 146.54, resulting in a total investment of S/1 146 014.68. For the financial evaluation, 60% of equity capital was considered and 40% financed for 5 years with an annual interest of 15%. According to the economic evaluation, there is a net present value of S/321 067.20, 28% internal rate of return, a benefit-cost ratio of 1.28 and the payback period will be 3 years, 8 months and 26 days. The financial evaluation indicates that there is S/353 027.94 of net present value, 34% internal rate of return, benefit-cost ratio of 1.51 and the recovery period will be 3 years, 6 months and 18 days. Regarding the social evaluation of the project, it was possible to analyze that to generate a job an average S/71 600.84; must be invested, for each sol invested, S / 3.84 of added value is obtained and to generate S /1.00 of value added S/ 0.26 investment is required.